An oscillation criterion for delay differential equations with several non-monotone arguments. (September 2016) - Akca, H.; Chatzarakis, G.E.; Stavroulakis, I.P.
Abstract: The oscillatory behavior of the solutions to a differential equation with several non-monotone delay arguments and non-negative coefficients is studied. A new sufficient oscillation condition, involving lim sup, is obtained. An example illustrating the significance of the result is also given.